Proceedings of the 50th Hawaii International Conference on System Sciences (2017) 2017
DOI: 10.24251/hicss.2017.589
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise Architecture Planning: Analyses of Requirements from Practice and Research

Abstract: Enterprise architecture management (EAM)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 24 publications
(27 reference statements)
0
21
0
Order By: Relevance
“…Enterprise architecture metamodels are often used to run different simulations and analyses [22], [23], which requires granular and up-to-date information [24]. Up to date information is critical for the success of enterprise transformation projects [8].…”
Section: Automated and Multi-source Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Enterprise architecture metamodels are often used to run different simulations and analyses [22], [23], which requires granular and up-to-date information [24]. Up to date information is critical for the success of enterprise transformation projects [8].…”
Section: Automated and Multi-source Modelingmentioning
confidence: 99%
“…The respondents prioritized correct data granularity, consistency, and being able to identify the source of data. Nowakowski et al [8] found in their enterprise architecture management requirements study that optimal tools need to support heterogeneous data because enterprise data are available in different forms and spread over multiple repositories.…”
Section: Automated and Multi-source Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research indicates low use of EAs for decision-making in organizations [1,15,22], in particular for visualizing and, hence, understanding complex IT landscapes [8,27,46]. Potential reasons for this include the limited perceived usefulness of EA visualizations, which are often characterized by their complexity [32], lack of focus [8], an inappropriate level of abstraction [27,46], or insufficient tool support [27]. In sum, this inhibits the effective use of EAs for decision-making [6], so that stakeholders often find the added value of EA visualizations to be rather low [15,32].…”
Section: Introductionmentioning
confidence: 99%
“…The absence of a reliable and up-todate documentation can result in slow error detection, loss of traceability of changes and misguided planning processes due to poor information situations. Ultimately, these issues can lead to problems which cause very high costs for the companies if they remain unaddressed [30,51].…”
mentioning
confidence: 99%